Source Apportionment of Soil Heavy Metal Pollution in the Yangtze River Basin Based on the Multiscale Geographically Weighted Spatial Lag Model - Yan, Fengying (Transactions on Environment, Energy and Earth Sciences, 2026)
As a crucial agricultural base, economic belt, and ecological barrier in China, the Yangtze River Basin is increasingly plagued by soil heavy metal pollution due to the combination of complex natural geographical conditions and intensive human activities. Based on soil heavy metal (As, Cd, Cr, Cu, Hg, Ni, Pb, Zn) content data from 906 sampling sites in the Yangtze River Basin from 2000 to 2020, this study integrated 11 explanatory variables from four categories (topography, land use, socio-economy, and meteorology) to construct three models: Geographically Weighted Regression (GWR), Multiscale Geographically Weighted Regression (MGWR), and Multiscale Geographically Weighted Spatial Lag Model (MGWR-VSLR). The spatial distribution characteristics and driving mechanisms of heavy metal pollution were systematically analyzed.Results showed MGWR - VSLR model excelled in R² and AICc, capturing heavy metal pollution’s spatial features. As and Hg pollution were affected by different factors. Spatial lag term indicated cross - regional influence. Soil heavy metal pollution in Yangtze River Basin results from natural and human factors. The research aids prevention and green development.